Reasoning Habits of Students through Realistic Mathematics Problems - Nadya Salsabila; Dewi Hamidah; Eka Resti Wulan (JME (Journal of Mathematics Education), 2022)
A realistic math problem is one of the math problems whose solution requires a reasoning habit. Reasoning ability will increase if students often practice their reasoning habits. By solving realistic math problems, it is expected that students’ reasoning habits can be trained well. This study aims to describe the reasoning habits of class VIII students of MTs Sunan Kalijogo Kranding Kediri Regency, East Java, Indonesia in solving realistic math problems in terms of 4 stages of reasoning habits. This study uses a qualitative approach with a descriptive type of research. The data collection technique in this study used a mathematical reasoning ability test sheet and interviews. The subjects in this study were students of class VIII F MTs Sunan Kalijogo Kranding, totaling 28 students, then three students with high, medium, and low categories of reasoning habits were taken to conduct interviews. The results of this study indicate that students with high-category reasoning habits can fulfill the four stages of reasoning habits. Students with reasoning habits in the medium category can fulfill two stages of reasoning habits. Students with low-category reasoning habits are not able to fulfill the four stages of reasoning habits. The results of this study are useful for choosing the right learning method in improving students' reasoning abilities, such as using realistic mathematics learning or Project Based Learning (PBL)